EFL Teacher’s Beliefs about Sociolinguistic Competence: : A Qualitative Case Study in Indonesian Formal English Pedagogy - Edi Ramawijaya Putra (Lingua Cultura, 2021)
The research aimed to explore beliefs of sociolinguistic competence from Indonesian EFL (English as a Foreign Language) teachers. Two teachers were carefully chosen to participate in the research. Data were collected through semi-structured interviews, analyzed, and interpreted using the critical descriptive method. The research finds that EFL teachers express their beliefs in various terms, ideologies, and perspectives. The result indicates that the EFL teachers’ beliefs about sociolinguistic competence are equivalent to the concepts of spatial repertoire, principled-polycentrism, resourceful speakers, and sociolinguistics as mobility. It also indicates that EFL teachers’ pedagogical affordances in determining learning objectives, selecting materials and media for learning, implementing classroom strategies, and choosing appropriate evaluation for their teaching are influenced by their beliefs of sociolinguistic competence. The research suggests that Indonesian EFL teachers should be awarded the freedom to develop sociolinguistic competence based on their classroom context and learners’ heterogeneity. With the presence of a national curriculum (known as K13) that gives more spaces for sociolinguistic competence to take place, teachers should transform their paradigm of seeing classroom interaction in EFL classroom to be more sociolinguistically-aware to transform the static, pre-determined, and motionless definition of sociolinguistic competence to a more dynamic, fluid, and varying. These transformations can be made by imparting sociolinguistic competence in teachers’ education and teachers’ professional development programs.